COVID-19 vaccination-related attendance at a pediatric emergency department in Singapore among 12- to 18-year old adolescents - Nicholas Beng Hui Ng; Gayle Fleur Appleby; Xin Yi Thong; Sze Kiat Alan Ong; Stephanie Zhen Wan Hii; Ian Kai Zhi Tan; Sharad Mohite; Pao Tang Kao (Pediatrics and Neonatology)
Background: Singapore was one of the first countries to begin COVID-19 vaccination with the BNT162b2 vaccine for adolescents aged 12–18 years. This study evaluates the incidence of COVID-19 vaccine related attendances to a Pediatric Emergency Department (PED) to understand post-vaccination health behaviors among adolescents. Methods: This was a retrospective review of electronic medical records over a 4 month period, from the start of the adolescent vaccination drive to when more than 85% of this group had been fully vaccinated. Results: The incidence of COVID-19 vaccination-related presentations to our PED was 3.1% over 4 months (291 of 9387 PED attendances), with a peak daily incidence of 15.4% (14 of 91 attendances). Presentations were characterized by severity into: severe (3.4%), moderate (7.9%) or mild (88.7%) based on predefined criteria. The most common presenting complaints were chest pain (58.8%), dyspnea (28.2%) and palpitations (22.6%). Hospitalization was required in only 6.2% of attendances. Patients with moderate-severe presentations were 0.7 years older (p = 0.030), more likely to have underlying drug allergies (p = 0.048) and had higher rates of hospitalization (p < 0.005) compared to mild presentations. Despite concerns of cardiac inflammation, chest pain related attendances were less likely to be severe (p < 0.005) with reduced hospitalization need (p = 0.043) compared to other presentations. Investigations beyond clinical assessment comprised 91% of attendances, but abnormalities were only found in 6.4% cases. Conclusion: Our study supports current evidence that COVID-19 vaccination is safe amongst adolescents. We highlight the health behaviors among adolescents post-vaccination, which is partly driven by media reports on vaccine side effects and an element of anxiety. While most of the presentations were mild, these can have implications on health resource utilization, particularly in an ongoing pandemic. As healthcare workers, we have an ongoing role to ensure accurate information on vaccine safety is communicated effectively to the public.